2018
DOI: 10.1039/c7bm00853h
|View full text |Cite
|
Sign up to set email alerts
|

Cell density overrides the effect of substrate stiffness on human mesenchymal stem cells’ morphology and proliferation

Abstract: Cell–cell interaction via substrate deformation in turn modifies cellular response to substrate rigidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 37 publications
4
55
1
Order By: Relevance
“…Spatial distribution of cells in monolayer culture is often observed . The different spatial distribution in culture vessel can affect growth kinetics.…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
See 4 more Smart Citations
“…Spatial distribution of cells in monolayer culture is often observed . The different spatial distribution in culture vessel can affect growth kinetics.…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
“…The different spatial distribution in culture vessel can affect growth kinetics. Recent experiments on seeding density and seeding uniformity have demonstrated that depending on the distance between the neighboring cells, the mechano‐response of a cell may vary dramatically . At low seeding density, cells are located far from each other and when dividing, each form clonal colonies.…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
See 3 more Smart Citations